Evidence-based practice utilisation and its associated factors among nurses working at public hospitals in West Shoa zone, central Ethiopia: a cross-sectional study - Yohanis Megersa; Abebe Dechasa; Abera Shibru; Lema Mideksa; Meseret Robi Tura (BMJ Open)
Objective The aim of this study was to assess the utilisation of evidence-based practice (EBP) and its associated factors among nurses working in public hospitals of West Shoa zone, Oromia, central Ethiopia, in 2021.Design Institution-based cross-sectional study.Setting Government hospitals including four primary hospitals, three general hospitals and a referral hospital. The study was conducted between 10 August and 30 August 2021.Participants 418 randomly selected nurses working in public hospitals of West Shoa. Data were collected via a structured, self-administered questionnaire, entered into EpiData V.3.1 and exported to SPSS V.26 for analysis.Outcome measure Utilisation of EBP (good/poor).Results 52.4% (95% CI 47.6% to 57.3%) of nurses had good EBP utilisation. Level of hospital (adjusted OR (AOR) 0.456 (95% CI 0.253 to 0.821)), administrative position (AOR 2.7 (1.09 to 6.69)), level of education (AOR 0.353 (0.181 to 0.686)), knowledge about EBP (AOR 1.785, (1.13 to 2.82)), availability of time (AOR 0.523 (0.28 to 0.96)), and cooperative and supportive colleagues (AOR 0.429 (0.235 to 0.783)) were associated with good utilisation of evidence-based nursing practice.Conclusion The utilisation of EBP among nurses is low. Level of education, knowledge about EBP, sufficient time at the workplace, and cooperative and supportive colleagues were among the factors associated with good EBP utilisation. The healthcare system in general, hospital management specifically, needs to design strategies to improve evidence-based nursing practice in the area.